Responsabilidad social en los medios de comunicación: ¿utopía o realidad? Algunos pasos a tomar en cuenta para lograr una adecuada gestión - Ramírez Lozano, Julianna Paola (2012)
The importance of Social Responsibility in Media is an issue that is in constant debate inside and outside Media. This concern about the impact of the information they diffuse to their public. As it is widely known, they have a strong influence in the Public Opinion on citizenship. In other words, the media has to be responsible not only for the information but also for the opinion they offer. When we refer to Social Responsibility, this implies a new concept in the model of management of the company or organization. Concretely, when the organization voluntarily assume ethics, by means of actions and campaigns, in the relationship with their environment and with each of their stakeholders. In this article, we make a reflection about the meaning and the importance of the management of social responsibility in media. We will remark some cases and testimonies from which we can study in detail the most important items to obtain an effective management of social responsibility in media. In addition to this, we will present some indicators from which it is possible to measure social responsibility in media considering also previous research by the author of this article about the cases of the following Peruvian companies: ATV, Radio Capital and Perú.21.